Performance and emission analysis of diesel engine with design modifications on piston crown. Issue 12 (14th October 2020) - Vijaya Kumar, K.; Shailesh, P.; Srinivasa Raghavan, K.; Ranga Babu, J. A.; Ravi Kumar, P.
Abstract : The present work aims to enhance the performance of the existing diesel engine by modifying the piston design. Swirl piston is used to induce turbulence as an active enhancement technique. The engine is run at 250 bar injection pressure and 17.5 compression ratio by varying the injection timings. A stirrer is introduced at the top of the piston so as to inculcate more turbulence to incoming charge that improves the fuel vaporisation rate. Whirling motion is created in the combustion chamber by rotating the blades on the cavity/bowl of the reciprocating piston head. A simple link mechanism is provided to convert the oscillatory motion of connecting rod into the rotary motion of the vane. The experimental result clears that the brake-specific fuel consumption is reduced by 8.7%, brake thermal efficiency is enhanced by 9.4%, 11.8% of CO emissions are controlled and NO x emissions are controlled by 27% is observed with the modified piston compared to the normal piston at retarded injection timing.